2006
DOI: 10.1097/00001813-200603000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylation-associated silencing of the death-associated protein kinase gene on nasopharyngeal carcinoma

Abstract: Death-associated protein kinase (DAPK) is a Ca/calmodulin-regulated serine/threonine kinase and a positive mediator of apoptosis. Loss of expression of the DAPK gene by aberrant promoter methylation may play an important role in cancer development and progression. The aim of this study was to investigate the frequency of gene promoter methylation of DAPK in nasopharyngeal carcinoma (NPC) and the effect of 5-Aza-2'-deoxycytidine (5-Aza-CdR), a demethylating agent, on CNE cells, a human nasopharyngeal carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The CNE cell line was obtained from the Institute of Biochemistry and Cell Biology, Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences. 18 CNE cells were maintained in RPMI 1640 with 10% FBS in a humidified 37°C incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The CNE cell line was obtained from the Institute of Biochemistry and Cell Biology, Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences. 18 CNE cells were maintained in RPMI 1640 with 10% FBS in a humidified 37°C incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, DAPK (but not CDH1) showed consistent results across studies, irrespective of sample type and methylation method. The three genes, CDH1, HIC1, and DAPK, resulting from our study are all plausibly associated with cervical carcinogenesis and are reported to be methylated and silenced in cancers at various other sites (49)(50)(51).…”
Section: Discussionmentioning
confidence: 90%
“…3p and 9p abnormalities have been identified in low-grade dysplastic lesions and normal nasopharyngeal mucosa of individuals at high risk indicating that these genetic changes are early events in the pathogenesis of NPC [10,17,20,33]. Other genes frequently inactivated by promoter methylation in NPC include TSCL1 at 11q23 and EDNRB at 13q22, E-cadherin, and death-associated protein kinase (DAPK) [34][35][36]. Gene expression profiling has shown dysregulation of the PI3K/Akt, WNT/b-catenin, TGF-b, and MAPK signaling pathways in NPC with upregulation of NF-jB2, survivin, Bcl-2 upregulation, nuclear accumulation of bcatenin, and dysregulation of integrins [37].…”
Section: Molecular Genetic Alterationsmentioning
confidence: 99%